The role of cell–substrate interaction in regulating osteoclast activation: potential implications in targeting bone loss in rheumatoid arthritis. (7th December 2009) - McHugh, K P; Shen, Z; Crotti, T N; Flannery, M R; O'Sullivan, R P; Purdue, P E; Goldring, S R
Abstract : Analysis of tissues retrieved from the bone–pannus interface from patients with rheumatoid arthritis (RA) and studies in animal models of inflammatory arthritis provide strong evidence that osteoclasts, the cells that are essential for physiological bone resorption, are responsible for articular bone destruction in RA. However, current treatments that specifically target osteoclast-mediated bone resorption in RA have not been successful in preventing bone erosions, and new therapeutic strategies are needed. It has been noted that, although osteoclast precursors are present within the bone microenvironment at sites of pathological bone resorption, cells expressing the full morphological and functional properties of mature osteoclasts are restricted to the immediate bone surface and adjacent calcified cartilage. These findings provide evidence that, in addition to requirements for specific cytokines, interaction of osteoclast precursors with these mineralised matrices results in activation of specific signal pathways and the induction of unique gene products that are essential for terminal osteoclast differentiation and activation. These studies are designed to define the gene products and signalling pathways regulated by bone and calcified cartilage, to identify new molecular targets and novel therapeutic approaches for preventing osteoclast-mediated joint destruction in RA and related forms of pathological bone loss.